Pengaruh Kepemimpinan Transformasional dan Manajemen Pengetahuan terhadap Kinerja Organisasi: Organisasi Pembelajaran sebagai Mediator - Indra Muis; Puji Isyanto (Politeknik Ganesha Medan, 2022)
This study aims to explain the implementation of transformational leadership, knowledge management, learning organization, and organizational performance at private universities in West Java province and examine the effect of transformational leadership and knowledge management on organizational performance mediated by learning organization. The unit of analysis is the head of a private university campus in West Java Province, Indonesia. Respondents were 38 rectors and vice rectors from 59 private universities and the sampling technique is simple random sampling. Data are analyzed by using Partial Least Square (PLS) technique. The results show that all the measured independent variables and the mediator have very good values, but the dependent variable has good values ??and is still needed to be improved. In addition, transformational leadership and knowledge management have a significant and positive effect on learning organization. Learning organization also has a significant and positive effect on organizational performance. It can be concluded that all higher education leaders need to apply transformational leadership, knowledge management and learning organizations to improve their organizational performance. Leaders at the university level need to encourage all employees to develop learning strategies and provide learning opportunities for their employees. In addition, they also need to develop open discussion and communication between employees so that employees can share knowledge and skills to solve problems they face in doing their jobs.